1) Решить уравнение
x^4 - 2x^3 + x - 42 = 0
x^4 - 2x^3 + x^2 - x^2 + x - 42 = 0
(x^2 - x)^2 - (x^2 - x) - 42 = 0
Замена x^2 - x = y
y^2 - y - 42 = 0
(y - 7)(y + 6) = 0
Обратная замена y = x^2 - x
a) x^2 - x - 7 = 0
D = 1 + 4*7 = 29
x1 = (1 - √29)/2; x2 = (1 + √29)/2
b) x^2 - x + 6 = 0
Это уравнение корней не имеет.
Ответ: x1 = (1 - √29)/2; x2 = (1 + √29)/2
2) Дано: (x+y)/(x-y) + (x-y)/(x+y) = 3
Найти (x^2+y^2)/(x^2-y^2) + (x^2-y^2)/(x^2+y^2)
Решение: Приводим к общему знаменателю:
![\frac{(x+y)^2 + (x-y)^2}{(x-y)(x+y)}=\frac{x^2+2xy+y^2+x^2-2xy+y^2}{x^2-y^2} = \frac{2x^2+2y^2}{x^2-y^2} =3 \frac{(x+y)^2 + (x-y)^2}{(x-y)(x+y)}=\frac{x^2+2xy+y^2+x^2-2xy+y^2}{x^2-y^2} = \frac{2x^2+2y^2}{x^2-y^2} =3](https://tex.z-dn.net/?f=%5Cfrac%7B%28x%2By%29%5E2%20%2B%20%28x-y%29%5E2%7D%7B%28x-y%29%28x%2By%29%7D%3D%5Cfrac%7Bx%5E2%2B2xy%2By%5E2%2Bx%5E2-2xy%2By%5E2%7D%7Bx%5E2-y%5E2%7D%20%3D%20%5Cfrac%7B2x%5E2%2B2y%5E2%7D%7Bx%5E2-y%5E2%7D%20%3D3)
Отсюда
(x^2+y^2)/(x^2-y^2) = 3/2
(x^2-y^2)/(x^2+y^2) = 2/3
Вторая сумма дробей равна 3/2 + 2/3 = 9/6 + 4/6 = 13/6 = 2 1/6